Grieving Our Way Back to Meaningfulness. (October 2021) - Cholbi, Michael
Abstract: The deaths of those on whom our practical identities rely generate a sense of disorientation or alienation from the world seemingly at odds with life being meaningful. In the terms put forth in Cheshire Calhoun's recent account of meaningfulness in life, because their existence serves as a metaphysical presupposition of our practical identities, their deaths threaten to upend a background frame of agency against which much of our choice and deliberation takes place. Here I argue for a dual role for grief in addressing this threat to life's meaningfulness. Inasmuch as grief's object is the loss of our relationship with the deceased as it was prior to their death, grief serves to alert us to the threat to our practical identities that their deaths pose to us and motivates us to defuse this threat by revising our practical identities to reflect the modification in our relationship necessitated by their deaths. Simultaneously, the emotional complexity and richness of grief episodes provides an abundance of normative evidence regarding our relationship with the deceased and our practical identities, evidence that can enable us to re-establish our practical identities and thereby recover a sense of our lives as meaningful.